The Role and the Regulation of NLRP3 Inflammasome in Irritable Bowel Syndrome: A Narrative Review - Arezina Kasti; Konstantinos Katsas; Maroulla D. Nikolaki; Konstantinos Triantafyllou (Microorganisms)
Irritable bowel syndrome (IBS) is a chronic disorder of the gastrointestinal tract. Its pathogenesis involves multiple factors, including visceral hypersensitivity and immune activation. NLRP3 inflammasome is part of the nucleotide-binding oligomerization domain-like receptor (NLR) family, a crucial component of the innate immune system. Preclinical studies have demonstrated that inhibiting NLRP3 reduces visceral sensitivity and IBS symptoms, like abdominal pain, and diarrhea, suggesting that targeting the NLRP3 might represent a novel therapeutic approach for IBS. This review aims to assess the NLRP3 inhibitors (tranilast, β-hydroxybutyrate, Chang-Kang-fang, paeoniflorin, coptisine, BAY 11-7082, and Bifidobacterium longum), highlighting the signaling pathways, and their potential role in IBS symptoms management was assessed. Although premature, knowledge of the action of synthetic small molecules, phytochemicals, organic compounds, and probiotics might make NLRP3 a new therapeutic target in the quiver of physicians’ therapeutic choices for IBS symptoms management.